1998
DOI: 10.1093/ndt/13.4.962
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal solute transport predicts survival on CAPD independently of residual renal function

Abstract: There is good reason to believe that high peritoneal solute transport is an independent marker of poor outcome in CAPD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
156
3
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(165 citation statements)
references
References 1 publication
5
156
3
1
Order By: Relevance
“…Peritoneal membrane transport status at baseline had no effect on outcome, unlike in previous studies of patients on CAPD (4,5,34). High transport status in CAPD results in poor UF with consequent fluid overload.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Peritoneal membrane transport status at baseline had no effect on outcome, unlike in previous studies of patients on CAPD (4,5,34). High transport status in CAPD results in poor UF with consequent fluid overload.…”
Section: Discussioncontrasting
confidence: 63%
“…The patients in this study were on continuous ambulatory peritoneal dialysis (CAPD) and had significant residual renal function, so small solute clearances achieved represented a combination of dialysis and renal clearance. The CANUSA study confirmed data from other studies (4,5) suggesting that patients on CAPD with high membrane permeability had increased mortality, possibly because of poor ultrafiltration (UF) and consequent fluid overload.…”
supporting
confidence: 82%
“…Our PD population was censored in 1998, at which time a survival analysis and description of longitudinal membrane function were published (16). Since 1998, increasing proportions of patients were treated with automated PD (APD), particularly when anuric, as described in the European Automated Peritoneal Dialysis Outcome Study (EAPOS) (9).…”
Section: Study Design and Patient Populationmentioning
confidence: 99%
“…Here we determined the association between patient survival and both solute transport and Pcl, measured and calculated independently, in a prospective, single-center cohort that had previously reported worse outcomes in patients with fPTS (16). We explored the relationship among peritoneal protein leak, comorbidity, and BP.…”
mentioning
confidence: 99%
“…Unfortunately, PD treatment frequently results in progressive decline of ultrafiltration capacity of the peritoneum usually associated with histological changes and loss of peritoneal integrity (Davies et al 1998). Pathological changes in the peritoneum are mainly the result of the toxic properties of standard low pH PD fluids (PDF) containing high levels of the osmotic agent glucose and its degradation products (GDP) (Leung et al 2005;Amore et al 2003).…”
Section: Introductionmentioning
confidence: 99%